A Study on Self Esteem of Women with HIV Positive with Special Reference to Amala Hospital, Thrissur - Deena Joseph (Journal of Social Work Education and Practice, 2016)
Health forms a major aspect in the well being and full functioning of an individual. Due to manifold reasons this aspect of health has been affected in different dimensions. New types of diseases are appearing and old diseases affect human at different levels. One of the major killer disease conquering lives of millions is AIDS. Despite over twenty years of research with billions of dollars spent each year, the conventional medical establishment's a war on AIDS has been a dismal failure. Today, we are no closer to understanding the underlying causes for the rapid rise of AIDS rates or to finding fate and effective treatments. Most people continue to equate AIDS with death, or at the very least on excruciating journey back to health filled with physical debilitation and pain. The present study will deal the self esteem of AIDS patients, the level of patients self esteem determines how they operate in their life, how they interact with others, spouse, children, friends and strangers. It determines their goals and what they strive, for, their achievement, and their satisfaction and their happiness in life.